2023
DOI: 10.1007/s12055-023-01518-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Enhanced Recovery After Surgery program for thoracic surgery in a developing country

Abstract: Purpose Enhanced Recovery After Surgery (ERAS) is a strategy used to improve perioperative outcomes and reduce complications. However, data on the efficacy of ERAS in thoracic surgery in developing countries are limited. The current study aimed to validate the benefits of ERAS among patients at a single institution. Methods This was a retrospective study of patients who underwent pulmonary resection at Vajira Hospital, Bangkok, Thailand, between 2016 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Prolonged immobilization increases bronchial secretions; increases the risk of atelectasis, pulmonary infection, and thromboembolism; prolongs hospitalization; and reduces patient self-confidence [ 5 ]. Mobilization and active participation of patients were important to optimize analgesia and improve postoperative outcomes [ 4 , 17 , 18 ]. Early discontinuation of bed rest and mobility improved pain control and increased the efficacy of cough and secretion clearance [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged immobilization increases bronchial secretions; increases the risk of atelectasis, pulmonary infection, and thromboembolism; prolongs hospitalization; and reduces patient self-confidence [ 5 ]. Mobilization and active participation of patients were important to optimize analgesia and improve postoperative outcomes [ 4 , 17 , 18 ]. Early discontinuation of bed rest and mobility improved pain control and increased the efficacy of cough and secretion clearance [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various analgesic agents and procedures have been used to control severe pain and agitation after extubation. Although some authors suggest peripheral locoregional analgesia (paravertebral block, serratus plane block, and intercostal block), paravertebral or epidural blocks were not performed to facilitate mobilization [ 7 , 17 ]. The side effects of opioids include somnolence, hypotension, and postoperative nausea and vomiting [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is significant variation in the included observational trials regarding sample size (range of 83 to 10,021 patients), hypothesis (ERAS vs historical control; impact of compliance with ERAS and outcomes), and design (prospective with matched historical controls, entirely retrospective). Of the included 26 observational trials, 21 reported the effect of ERAS on overall complications, with seven studies demonstrating that implementation of an ERAS protocol led to reduced overall post-operative morbidity [3,6,[9][10][11][12]14,15,[18][19][20][21]23,[25][26][27]28,29,[30][31][32]. Five of these studies were comparing the ERAS protocol to historical controls [3,9,10,11,31].…”
Section: Observational Studiesmentioning
confidence: 99%
“…Of the 26 included studies, 14 reported on mortality [12,13,16,18,19,22,23,26,27,29,[30][31][32]. The only study to report a significant difference in mortality was the study by Alwarti et al, a retrospective cohort study published in 2021 [13].…”
Section: Observational Trialsmentioning
confidence: 99%
“…As such, the ERASÒ society ( www.erassociety.org ) has developed evidence driven guidelines for the successful implementation and audit of these perioperative pathways in various specialties. Although its roots began in colorectal surgery multiple surgical fields such as cardiothoracic ( 3 ), gynaecology ( 4 ) and orthopaedic joint surgery ( 5 ) have applied speciality-specific protocols with published successes over the last decade. More recently its implementation and assessment has been adopted to spine surgery across the world, but in Australia it still remains in its infancy.…”
Section: Introductionmentioning
confidence: 99%